Analisis Metode K-Medoids Pada Penjualan Produk Smartphone Vivo Di Kota Pematangsiantar - Mita Yustika; Agus Perdana Windarto; Yuegilion Pranavarna Purba (LPPM STIKOM Tunas Bangsa, 2021)
Globalization is a very promising era of openness and freedom, where a communication which is a means to obtain information is expected to be carried out easily and effectively. One of the communication media in question is a cellphone. The users of cellphones or cellphones used to be limited to the elite, but for now it has begun to penetrate various circles of society ranging from students, university students, civil servants and even ordinary people who have used it... K-Medoids Clustering is one of the one technique of one of the data mining functionality, the clustering algorithm is an algorithm for grouping a number of data into certain data groups (clusters). While data mining, often referred to as Knowledge Discovery In Database (KDD) is an activity that includes the collection, use of historical data to find regularities, patterns or relationships in large data sets aimed at finding out the Vivo Smartphone brand that is selling well in the market so that it can be done. early procurement. From this study, it was found that Vivo smartphones with the brand S1 Pro 8+128, V17 Pro, V19 8+128GB, V19 8+256GB, Y11 2+32GB, Y12 3+64GB, Y17 4+128GB, Y19 6+128GB are brands which sold a lot. With the results obtained can provide information to PT. Vivo is improving its service even better by increasing the stock of Vivo smartphones which are in great demand, especially in the city of Pematangsiantar